Cognitive load theory - Sweller, John.; Ayres, Paul.; Kalyuga, Slava; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Effective instructional design depends on the close study of human cognitive architecture?the processes and structures that allow people to acquire and use knowledge. Without this background, we might recognize that a teaching strategy is successful, but have no understanding as to why it works, or how it might be improved.
Electronic reproduction.
Keywords: Cognitive learning; Educational psychology; Instructional systems -- Design; Electronic books